Mixing mother tongue and English: Exploring the reasons and functions of code mixing - Kanthimathi, K. (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
India is a multilingual country where code mixing is a strategy used by speakers of different indigenous languages. Mixing of the mother tongue and English is a common speech behaviour that occurs in the discourse of educated bilinguals. There are various factors that influence the use of English in a mother tongue discourse. This paper explores the various reasons for code mixing, and the domains where a mixed code is preferred by Tamil speakers. The research design combines quantitative and qualitative approaches. The data for this study was collected by means of a questionnaire. The participants were students from different colleges in Tamil Nadu. The students were required to self-report their awareness of the frequency and purposes of using code mixing in different situations in their daily lives. This study was conducted on college students among whom code mixing is a practice. The results showed that the degree of code mixing depends on various factors such as amount of exposure to English, the medium of instruction in school and the frequency of language used in different domains, contexts and topics of discussion. This paper throws light on the fact that mixing the mother tongue and English facilitates communication and is performed for certain practical reasons.